2012
DOI: 10.1007/s00373-012-1193-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Edge Connectivity of Direct Products with Dense Graphs

Abstract: Let κ ′ (G) be the edge connectivity of G and G×H the direct product of G and H. Let H be an arbitrary dense graph with minimal degree δ(H) > |H|/2. We prove that for any graphwhere e(H) denotes the number of edges in H. In addition, the structure of minimum edge cuts is described. As an application, we present a necessary and sufficient condition for G × K n (n ≥ 3) to be super edge connected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Mamut and Vumar [14] proved that κ(K m × K n ) = (m − 1)(n − 1) where m ≥ n ≥ 2. In [9], it was shown that if n ≥ 3 and G is a bipartite graph, then κ(G×K n ) = min{nκ(G), (n − 1)δ(G)}, and furthermore, the authors also conjectured that this is true for all nontrivial graph G. Later, this conjecture was confirmed independently by Wang and Wu [17] and Wang and Xue [18].…”
Section: Introductionmentioning
confidence: 92%
“…Mamut and Vumar [14] proved that κ(K m × K n ) = (m − 1)(n − 1) where m ≥ n ≥ 2. In [9], it was shown that if n ≥ 3 and G is a bipartite graph, then κ(G×K n ) = min{nκ(G), (n − 1)δ(G)}, and furthermore, the authors also conjectured that this is true for all nontrivial graph G. Later, this conjecture was confirmed independently by Wang and Wu [17] and Wang and Xue [18].…”
Section: Introductionmentioning
confidence: 92%
“…In [20] proved that G * is connected if G is connected and |S| < (n − 1)δ(G). In fact, when |S| = (n − 1)δ(G) here, we still get the result by using the same method in [20]. Proof.…”
Section: Lemma 1 ([21]mentioning
confidence: 99%
“…Guji and Vumar [10] presented the connectivity of Kronecker product of a bipartite graph and a complete graph and they proposed to investigate the connectivity of Kronecker product of a nontrivial graph and a complete graph. Recently, Wang and Xue [20] settled the problem and they obtained the following result.…”
Section: Introduction and Terminologymentioning
confidence: 99%
“…Therefore it is not possible to express the connectivity of the direct product of graphs exclusively in terms of connectivities (and minimum degree, size and order) of the factors. There is an extensive list of articles on connectivity of direct products of graphs where the authors consider special examples and determine their connectivity, or they obtain upper and lower bounds for the connectivity, or they study related concepts such as super connectivity, see [2,3,5,6,10,11,14,15,16,7]. In this article we settle the question of edge connectivity of direct products as well as the question about the structure of a minimum edge-cut in the direct product of graphs.…”
Section: Introductionmentioning
confidence: 99%